Detailed FE and DE Modelling of Stone Masonry Arch Bridges for the Assessment of Load-carrying Capacity. (2015) - Costa, C.; Arêde, A.; Morais, M.; Aníbal, A.
Abstract: This paper reports on numerical modelling strategies for assessment of the load capacity of stone arch bridges based on realistic knowledge of the constituent material properties. Detailed micro-models based on FEM and DEM with suitable nonlinear behaviour of the bridge materials are used to evaluate the bridge structural behaviour under incremental static loading. Simplified modelling strategies based on rigid blocks analysis is also used for comparative purposes. Results of laboratory testing performed to characterize the deformability and strength parameters of the bridge materials (masonry and infill) are used to support the structural analysis. The study comprised four existing road bridges located in the North of Portugal. Experimental modal identification of the bridge cases has also been included in the study with the aim of updating and validating the bridge models.